10th IEEE International Conference on Nano/Micro Engineered and Molecular Systems 2015
DOI: 10.1109/nems.2015.7147455
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting from human motion for wearable devices

Abstract: Energy harvesting technology provides a promising choice to replace the batteries used in modern wearable devices. This paper describes new kind of piezoelectric energy harvesting devices aiming for high power output at low frequency with broad bandwidth. By accessing the performance of the device at different frequencies, we have demonstrated two energy harvesting devices with power output at 10 microwatts level. A complete energy harvesting system is also designed to adjust the output voltage for practical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…21 Incorporating NEMS/MEMS sensors in clothing and developing more compact and flexible devices have gained popularity in the past few years. 22 The unique behavior of these devices makes them an attractive choice for a wide range of applications, from smart fabrics to flexible solar cells. 23−26 Traditionally, NEMS/MEMS produced filters, gears, and switches 27 by integrating them with optoelectronic, mechanical, thermal, radiofrequency, or microelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Incorporating NEMS/MEMS sensors in clothing and developing more compact and flexible devices have gained popularity in the past few years. 22 The unique behavior of these devices makes them an attractive choice for a wide range of applications, from smart fabrics to flexible solar cells. 23−26 Traditionally, NEMS/MEMS produced filters, gears, and switches 27 by integrating them with optoelectronic, mechanical, thermal, radiofrequency, or microelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found they can sense various physiological conditions . Incorporating NEMS/MEMS sensors in clothing and developing more compact and flexible devices have gained popularity in the past few years . The unique behavior of these devices makes them an attractive choice for a wide range of applications, from smart fabrics to flexible solar cells. …”
Section: Introductionmentioning
confidence: 99%
“…Through them, it is possible to recover and store energy from different energy sources in the human body. There is a wide variety of energy harvester technologies depending on their operation mode [19][20][21][22]. They are divided into categories: piezoelectric, thermoelectric, triboelectric, and solar fabrics [23][24][25].…”
Section: Introductionmentioning
confidence: 99%